(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2019)
This essay, composed for a history course on postwar America, argues that progressive factions should center their agendas around identities, such as race, instead of on general economic classifications. For more details, listen to the author’s reflection on the piece below.